PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS KIPIN SCHOOL PADA MATA PELAJARAN IPAS TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS 4 DI SDN CENGKLIK SURAKARTA - Lucky Damar Fawwazi; Oktiana Handini; Elinda Rizkasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aimed to examine the extent to which the use of Kipin School, a digital learning platform, contributes to improving the academic performance of fourth-grade students in Science and Social Studies subjects at SDN Cengklik, Surakarta. Kipin School offers a variety of interactive features designed to enhance students' understanding and make the learning process more engaging. The study employed a quantitative approach with a one-group pretest and posttest design. All fourth-grade students participated in the research, with one group receiving instruction through Kipin School, while another group served as a comparison. Data were collected through tests administered before and after the learning sessions and analyzed using a t-test to determine differences in learning outcomes. The results showed a significant improvement in the academic performance of students who used Kipin School. Therefore, it can be concluded that Kipin School has a positive impact on students' comprehension in Science and Social Studies.